Reinventing Public Leadership to Enhance Public Trust in Local Government Administration: A Case Study of the Rejang Lebong Regency Government for the 2025–2030 Period) - Tuti Handayani IS; Rina Julita; Yanuar Rikardo (CV. Era Digital Nusantara, 2026)
This study examines the reinvention of public leadership in enhancing public trust toward local government administration in Rejang Lebong Regency during the 2025–2030 leadership period. Public trust is an essential element in local governance because it influences policy legitimacy, citizen participation, and the effectiveness of public service delivery. In the context of regional government, public trust is closely related to the ability of leaders to promote transparency, accountability, responsiveness, innovation, and effective public communication. This study uses a qualitative method with a descriptive approach to analyze how public leadership renewal is practiced and how it contributes to strengthening community trust. Data are collected through observation, interviews, documentation, and literature study. The findings indicate that reinventing public leadership is not only related to changes in leadership style, but also to broader improvements in governance practices. Leadership innovation, transparent information, responsive public services, meaningful citizen participation, accountable decision-making, and clear public communication are important factors in building public confidence. The study concludes that leadership renewal in Rejang Lebong Regency can become a strategic foundation for creating a more adaptive, participatory, service-oriented, and trusted local government administration. This research is expected to contribute to the development of public administration studies and provide practical recommendations for improving local governance quality.